Adherence to Institutional Guidelines for Community and Nosocomial Pneumonia and Its Impact on In-hospital Mortality and 30-day Readmission in a Community Health System. (4th October 2017) - Lanza, David; Vyas, Nikunj; Levin, Todd; Pontiggia, Laura
Abstract: Background: Antimicrobial stewardship committee at Kennedy Health created novel pneumonia guidelines in 2016 which were based on local antibiogram and multi-drug resistant organism risk factors. The purpose of this study was to measure adherence to institutional treatment guidelines (ITG) and its impact on mortality and 30-day readmissions. Methods: An IRB approved retrospective chart review was conducted on patients admitted for > 24 hours with a confirmed diagnosis of bacterial pneumonia. Patients were included if they were ≥18 years old and diagnosed with community-acquired pneumonia (CAP) or hospital-acquired pneumonia (HAP) between April and September 2016. The primary objective of the study was to measure the adherence to ITG for CAP and HAP. The secondary objectives were to measure the in-hospital mortality and 30-day readmission rate between the adherent and non-adherent groups. A pre and post implementation analysis was performed focusing on rates of hospital acquired respiratory infection (HARI) rates, and overall antibiotic utilization. Results: There were 216 patients included in the study with CAP ( n = 128) and HAP ( n = 88). The rate of adherence to ITG was higher in CAP vs.. HAP (73.4% vs. 45.5%, P < 0.001). Although there was no difference observed in mortality between CAP and HAP (0.8% vs. 0.0%, P = 1.0), the rate of 30-day readmissions was lower in CAP vs. HAP (4.7% vs. 29.5%, P < 0.001). When comparing adherent and non-adherent groups, there was no difference in 30-day readmissions in patients with CAP (4.3% vs. 5.9%, P = 0.656) and HAP (30.9% vs. 26.1%, P = 0.613). There was a 32.1% decrease in anti-pseudomonal β-lactam usage in 2016 vs. 2015 (53.6 vs. 79 DOT/1000PD, P = 0.008). Fluoroquinolone utilization was decreased by 55.8% in 2016 vs. 2015 (39.6 vs. 89.6 DOT/1000PD, P < 0.001). Vancomycin utilization decreased by 28.4% in 2016 compared with 2015 (67.9 vs. 94.9, DOT/1000PD, P = 0.009). Comparing 2016 vs. 2015, we noticed a decrease in pseudomonas HARI rates (2% vs. 3%) however, an increase in MRSA HARI rates (1% vs. 0.2%). Conclusion: Adherence to ITG was shown to be higher for CAP compared with HAP. Although there was no difference seen in mortality between CAP and HAP, there was significantly lower 30-day readmissions in patients with CAP compared with HAP. Overall, antipseudomonal and anti-MRSA antibiotic utilization was decreased after ITG implementation. Disclosures: All authors: No reported disclosures.